Gamified Lecture Courses Improve Student Evaluations but Not Exam Scores - Nakada, Toyohisa (Frontiers in ICT, 2017)
Gamified lectures are defined as lectures formatted as games, for the purposes of this research. This paper presents an example of a traditional instruction-based lecture that was redesigned using a game-like design. First, confrontations specific to gaming situations were considered, to derive goals for students in a classroom. Students fought using a game system in these experiments. The teacher acted as a game administrator, and controlled all the game materials. He also became an interface between the game system and students. Redesigned lectures were compared with traditional instruction-based lectures for their effects on relieving student dissatisfaction with the classroom. The achievement levels of students showed no improvement in the gamified design compared to the traditional instruction-based format.